Working with autistic children and young people : a practical guide for speech and language therapists - Mordi, Sally, 1974- (Oxon: Routledge, 2024)
"This book focuses on appreciating the different language and communication style of autistic youngsters and discusses how therapists can respond to and support this to get the best out of their practice. Each chapter begins with a summary of key points and areas to focus on, includes 'what to do' ideas and mini case-studies to illustrate points, as well as signposting further reading. The book draws on relevant theory and offers practical insights to allow the therapist to develop confidence, knowledge and skills. Topics covered include: - identifying effective support, - emotional regulation, - working with technology, - specific groups such as girls with autism. Linking theory and practice in an engaging and easy-to-follow format, The book provides practical ideas that are immediately helpful for busy professionals to guide clinical decision making and intervention. It is an invaluable addition to the tool kit of any speech and language therapist, as well as other professionals wanting an overview of how to work with autistic children and young people in our neurodiverse society"--
Includes bibliographical references and index.
Keywords: Autistic children -- Language; Autistic children -- Means of communication; Speech therapy; Speech disorders in children